Evaluating the correlation of sclerostin levels with obesity and type 2 diabetes in a multiethnic population living in Kuwait - Alramah, Tahani; Cherian, Preethi; Al-Khairi, Irina; Abu-Farha, Mohamed; Thanaraj, Thangavel Alphonse; Albatineh, Ahmed N.; Safadi, Fayez; Ali, Hamad; Abdul-Ghani, Muhammad; Tuomilehto, Jaakko; Koistinen, Heikki A.; Al-Mulla, Fahd; et al. (Frontiers in Endocrinology, 2024)
Obesity and Type 2 Diabetes Mellitus (T2DM) are intricate metabolic disorders with a multifactorial etiology, often leading to a spectrum of complications. Recent research has highlighted the impact of these conditions on bone health, with a particular focus on the role of sclerostin (SOST), a protein molecule integral to bone metabolism. Elevated circulating levels of SOST have been observed in patients with T2DM compared to healthy individuals. This study aims to examine the circulating levels of SOST in a multiethnic population living in Kuwait and to elucidate the relationship between SOST levels, obesity, T2DM, and ethnic background. The study is a cross-sectional analysis of a large cohort of 2083 individuals living in Kuwait. The plasma level of SOST was measured using a bone panel multiplex assay. The study found a significant increase in SOST levels in individuals with T2DM (1008.3 pg/mL, IQR-648) compared to non-diabetic individuals (710.6 pg/mL, IQR-479). There was a significant gender difference in median SOST levels, with males exhibiting higher levels than females across various covariates (diabetes, IR, age, weight, and ethnicity). Notably, SOST levels varied significantly with ethnicity: Arabs (677.4 pg/mL, IQR-481.7), South Asians (914.6 pg/mL, IQR-515), and Southeast Asians (695.2 pg/mL, IQR-436.8). Furthermore, SOST levels showed a significant positive correlation with gender, age, waist circumference, systolic and diastolic blood pressure, fasting blood glucose, HbA1c, insulin, total cholesterol, triglycerides, HDL, LDL, ALT, and AST (p-Value ≥0.05). South Asian participants, who exhibited the highest SOST levels, demonstrated the most pronounced associations, even after adjusting for age, gender, BMI, and diabetes status (p-Value ≥0.05). The observed correlations of SOST with various clinical parameters suggest its significant role in the diabetic milieu, particularly pronounced in the South Asian population compared to other ethnic groups.